The Presence or Absence of Female Characters in Mary Shelley’s Frankenstein - Shahrzad Mohammad Hossein; Narges Raoufzadeh; Fatemeh Sadat Basirizadeh (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Mary Wollstonecraft Godwin Shelley (1979 – 1851), the daughter and later the wife of one of the keenest critics in England, wrote the novel Frankenstein (1818) when she was only nineteen years old. Since its publication, the novel has been the subject of many literary discussions due to the myriad controversial issues discovered in the novel in the light of different literary approaches; such as, eco-criticism, feminism, psychoanalysis, cultural studies, queer studies and post-colonial studies to name a few. This paper aims to discover whether it is a fact that the novel is flawed, mainly due to the absence of forceful female characters. The novel’s schematic arrangement of characters was deemed as deficient simply because, first of all, readers had developed the wrong kind of expectation from the author and secondly, they were not giving the novel the critical, observant reading that it deserved. Contrary to what a superficial reading of the work will reveal, this novel is not deficient at all if it comes to the presence of female characters. Instances from the novel can depict and illustrate this claim and it is only weak traditional readings of the novel which tend to overlook its intensely sexual materials. In the light of such findings, Frankenstein can be judged as one of the most bewildering, intricate works of literature of the Victorian era.